Thematic Priorities For Sustainable Development of Ukraine-Romania Cross-Border Cooperation (The Case Study of Chernivtsi Region) - Bohatyrets, Valentyna; Melnychuk, Liubov; Zoriy, Yaroslav (Modern Historical and Political Issues, 2020)
This paper seeks to investigate sustainable cross-border cooperation (CBC) as a distinctive model of interstate collaboration, embedded in the neighboring borderland regions of two or more countries. The focus of the research revolves around the establishment and further development of geostrategic, economic, cultural and scientific capacity of the Ukrainian-Romanian partnership as a fundamental construct in ensuring and strengthening the stability, security and cooperation in Europe. This research highlights Ukraine’s aspirations to establish, develop and diversify bilateral good-neighborly relations with Romania both regionally and internationally. The main objective is to elucidate Ukraine-Romania cross-border cooperation initiatives, inasmuch Ukraine-Romania CBC has been stirring up considerable interest in terms of its inexhaustible historical, cultural and spiritual ties. Furthermore, the similarity of the neighboring states’ strategic orientations grounds the basis for development and enhancement of Ukraine-Romania cooperation. The authors used desk research and quantitative research to conclude that Ukraine-Romania CBC has the impact not only on the EU and on Ukraine multi-vector foreign policy, but it also has the longer-term global consequences. In the light of the current reality, the idea of introducing and reinforcing the importance of Cross-Border Cooperation (CBC) sounds quite topical and relevant. This research considers a number of explanations for Ukraine-Romania Cross-Border Cooperation as a key element of the EU policy towards its neighbors. Besides, the subject of the research is considered from different perspectives in order to show the diversity and complexity of the Ukraine-Romania relations in view of the fact that sharing common borders we are presumed to find common solutions. As the research has demonstrated, the Ukraine-Romania cross border cooperation is a pivotal factor of boosting geostrategic, economic, political and cultural development for each participant country, largely depending on the neighboring countries’ cohesion and convergence. Significantly, there is an even stronger emphasis on the fact that while sharing the same borders, the countries share common interests and aspirations for economic thriving, cultural exchange, diplomatic ties and security, guaranteed by a legal framework. The findings of this study have a number of important implications for further development and enhancement of Ukraine-Romania cooperation. Accordingly, the research shows how imperative are the benefits of Romania as a strategic partner for outlining top priorities of Ukraine’s foreign policy.
Пріоритети сталого розвитку україно-румунського транскордонного співробітництва (на прикладі Чернівецької області)
Keywords: Ukraine; Romania; cross-border cooperation; interstate relations; Chernivtsi region; security; Europe